Implementasi Gagasan Islamisasi Ilmu Pengetahuan Kontemporer SMN al-Attas terhadap Teori Psikoanalisis Sigmund Freud: Implementation of SMN al-Attas' Concept of Islamization of Contemporary Science on Sigmund Freud's Psychoanalysis Theory - Adib Fattah Suntoro; Saniyya Khoirun Amala; Muhyiddin, Luthfi (Center of Islamic and Occidental Studies, 2024)
This article examines Sigmund Freud's psychoanalysis theory through the perspective of Syed Muhammad Naquib al-Attas' Islamization of Contemporary Science. This study is significant since Sigmund Freud's psychoanalysis theory contains several problems, particularly religious theology. Syed Muhammad Naquib al-Attas, a modern philosopher, proposed the idea of Islamization of Contemporary Science with the objective to liberating science from the hegemony of the secular Western worldview. The findings of this research, which used the critical-descriptive analysis approach, indicate that Sigmund Freud's psychoanalysis theory comprises a secular-atheistic worldview, which is evident in his views on God, religion, and morality. The idea of the human psychological structure that is better accordance with the Islamic worldview is discovered via the integration process, that is the human concept, consisted of al-rūḥ (spirit), al-‘aql (reason), al-nafs (soul), al-qalb (heart), and al-fithrah (instinct).